2018
DOI: 10.1101/316612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global landscape of mouse and human cytokine transcriptional regulation

Abstract: Cytokines play a central role in immune development, pathogen responses, and diseases. Cytokines are highly regulated at the transcriptional level by combinations of transcription factors (TFs) that recruit cofactors and the transcriptional machinery. Here, we review three decades of studies to generate a comprehensive database reporting 843 and 647 interactions between TFs and cytokines genes, in human and mouse respectively (http://cytreg.bu.edu). We provide a historic perspective on cytokine regulation disc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…IL32 and PROK2 were two of the most differentially expressed cytokine genes, as well as being present multiple times in the over‐represented categories of “Migration of cells,” “Inflammation of organ,” and “Mobilization of Ca 2+ ” ( Figure , Table ). Prior to initiation of these functional experiments, we performed a strict Bonferroni multiple testing correction ( P < 0.0002) for all cytokine genes in the human genome 30 . Of the 11 cytokine genes defined as significant by FDR ( Table ), 10 remained significant following Bonferroni correction, including IL32 and PROK2 .…”
Section: Resultsmentioning
confidence: 99%
“…IL32 and PROK2 were two of the most differentially expressed cytokine genes, as well as being present multiple times in the over‐represented categories of “Migration of cells,” “Inflammation of organ,” and “Mobilization of Ca 2+ ” ( Figure , Table ). Prior to initiation of these functional experiments, we performed a strict Bonferroni multiple testing correction ( P < 0.0002) for all cytokine genes in the human genome 30 . Of the 11 cytokine genes defined as significant by FDR ( Table ), 10 remained significant following Bonferroni correction, including IL32 and PROK2 .…”
Section: Resultsmentioning
confidence: 99%
“…Limitations to eY1H assays include that LTR chromatization may not be recapitulated in yeast, prey transcription factors may not have proper posttranslational modifications, and the screen does not capture heteromultimeric complexes. However, our previous studies examining transcriptional elements by eY1H had 30 to 60% validation rates for identified factors, comparable to, or better than, other methods, including ChIP-seq and motif prediction (26,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 53%